Life experiences and disease trajectories in women coexisting with ovarian cancer - Li-Yun Tsai; Jung-Mei Tsai; Shiow-Luan Tsay (Elsevier, 2020)
Objective: This study investigated the lived experiences of ovarian cancer survivors amid the disease trajectory and psychosocial adaptation. Materials and methods: Twenty-one women, all of whom were ovarian cancer survivors, were recruited from medical centers in Taiwan. In-depth, face-to-face, semi-structured interviews were conducted and transcribed verbatim from audio recordings. The sample size was determined by information saturation during data collection. The steps of data process and analysis were performed using Giorgi's phenomenology. Results: Three themes and 12 subthemes were extracted: (1) a depressed state, as if facing a fierce enemy: being sentenced to a death penalty like facing an insurmountable challenge; contradictory information and helplessness; turnaround for treatment decision; and facing stigmatization from society; (2) shadow of cancer recurrence: side-effects of cancer treatment; falling into desperation and frustration; worrying about cancer recurrence; and continuing to fight cancer; (3) a change of mindset to move forward: experiencing changes in outlook on life; activating the self-healing process; coexisting with cancer and treating it as a chronic disease; and experiencing physical and mental purification and enhancement. Conclusion: The conventional models caring for patients with ovarian cancer are based on disease and unable to meet their needs because the lengthy rehabilitation journey. Therefore, medical personnel should emphasize patients' medical autonomy and combine professional care and social resources to help patients developing adjustment strategies and establishing support systems in timely manner for body, mind, and soul of these patients. Keywords: Ovarian cancer survivors, Life experience, Disease trajectory, Phenomenology